Material removal in ultrasonic abrasive polishing of additive manufactured components - Jingsi, Wang; Liew, Pay Jun; Jiaqi, Zhu (MDPI AG, 2019)
Powder-based layered Additive Manufacturing (AM) techniques lead to high surface roughness, due to the balling and partial melting of powders, which cannot satisfy the requirements of design and practical use. Consequently, until there is a significant step-change in the resolution of AM technology, finishing processes will be a necessary step in the additive manufacturing process. In this work, ultrasonic abrasive polishing experiments are conducted with the aim of improving the surface quality of additive manufactured components. The roles of cavitation bubbles and abrasive particles in material removal are discussed. The impact action of abrasive particles is simulated using the Smoothed Particle Hydrodynamics (SPH) method. The effects of ultrasonic output power and the concentration of abrasive suspension on machining characteristics are also examined. It is found that the cavitation bubble collapse in ultrasonic polishing can remove the partially melted structures efficiently, and further roughness improvement could be obtained using the micro-cut and impact of abrasive particles in the slurry. An increase in the ultrasonic output power and abrasive concentration within a certain range lead to a more desirable polishing effect